A Study on Financial Capacity of Rural Jaffna from Dowry System for Economic Development - Santhirasegaram, S. (JUICE- 2012 University of Jaffna, 2012)
Principle objectives of this study are to asses the monetary value of dowry which is financial strength of region and to investigate the economic benefits of dowry to society. Most of the existing literatures explain that dowry system in Tamil society is social crime and adversely effect society. This study from a sample of rural Jaffna, Varany Eyattaly (J/343) during 2007-2011, shows that dowry system in Jaffna has been beneficial to Tamil society economically. Empirical findings show that single matrimony accumulates 5.49 million LKR worth saving as dowry in average. The major form of dowry is housing, average 2.44 million LKR and second one is cash 1.142 million LKR. Third one is jewelries average 0.852 million LKR. High and low land having average 0.42 million and 0.211 million LKR, respectively. Based on rural data, this study shows that average 23363.25 million LKR assets accumulated via dowry system in Jaffna district annually. This value of dowry may be more in urban than rural if reliable data will be collected. Key income source for accumulating saving for dowry is foreign remittance particularly earned from developed countries. The correlation between value of dowry and number of family members, living in developed countries is 67 percent. Correlation between value of the dowry and number of sisters as well as number of brothers are 49 percent and 56 percent respectively. Saving of Jaffna people for giving dowry is invested in house building, jewelries, land and bank deposit. Therefore, construction, real estate, banking and finance and jewelries related business in Jaffna are more active and profitable. Local and central governments can maintain a systematic tax system in these industries and increase their tax revenues. Tamil’s dowry culture has internal financial capacity for economic development. Political power for provincial government is needed for regulating this saving toward the economic development of this region.